Edukasi Upaya Pencegahan Perilaku Kekerasan pada Anak Usia Pre & Usia Sekolah di Panti Yauma Yatim dan Dhuafa Kemayoran Jakarta Pusat - Ernawati Ernawati; Nia Rosliany; Muchamad Ichrom Tobari; Zahwa Sabil Ramadhani; Kezia Ester Josephin (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Children as the nation's generation are a very important asset. Children have the potential to be human resources who will hold the journey of the Indonesian nation in the next few years. Violence prevention education can be provided as early as possible starting from preschool age. Preschool-aged children have a large amount of information at their disposal in a short period of time. The purpose of this activity is to provide education about the prevention of violence against children at the Yauma Orphanage, so that children and caregivers understand the forms of violence, how to prevent it, and create a safe environment for child development by measuring changes before and after the intervention. Pre-test and post-test, which calculate mean values and variations for each condition, are used to evaluate students' knowledge. Pareto analysis was also used to calculate the percentage increase in knowledge with the result of increasing child mobilization with an N-Gain score of 65.09961, the program showed that an educational approach that included pre-test and post-test increased students' knowledge about sexual violence prevention. As evidence of the success of this intervention, the pre and post results showed an increase in student knowledge of up to 85%. The program not only raises health awareness, but also teaches students more about how to apply violence to children in daily life. The conclusion in this activity can increase the health awareness of students at the Kemayoran Orphanage and Dhuafa Orphanage, Central Jakarta.